Microplastic and mesoplastic pollution in surface waters and beaches of the Canary Islands: A review - García Regalado, Andrea; Herrera, Alicia; Almeda, Rodrigo (Marine Pollution Bulletin, 2024)
The Canary Archipelago is a group of volcanic islands located in the North Atlantic Ocean with high marine biodiversity. This archipelago intercepts the Canary Current, the easternmost branch of the Azores Current in the North Atlantic Subtropical Gyre, which brings large amounts of litter from remote sources via oceanic transportation. It is, therefore, particularly vulnerable to marine plastic pollution. Here, we present a review of the available studies on mesoplastics and microplastics in the Canary Islands over the last decade to evaluate the level and distribution of plastic pollution in this archipelago. Specifically, we focused on data from beaches and surface waters to assess the pollution level among the different islands as well as between windward and leeward zones, and the main characteristics (size, type, colour, and polymer) of the plastics found in the Canary Islands. The concentrations of meso- and MPs on beaches ranged from 1.5 to 2972 items/m2 with a mean of 381 ± 721 items/m2. The concentration of MPs (>200 μm) in surface waters was highly variable with mean values of 998 × 103 ± 3364 × 103 items/km2 and 10 ± 31 items/m3. Plastic pollution in windward beaches was one order of magnitude significantly higher than in leeward beaches. The accumulation of MPs in surface waters was higher in the leeward zones of the high-elevation islands, corresponding to the Special Areas of Conservation (ZECs) and where the presence of marine litter windrows (MLW) has been reported. Microplastic fragments of polyethylene of the colour category “white/clear/uncoloured” were the most common type of plastic reported in both beaches and surface waters. More studies on the occurrence of MLW in ZECS and plastic pollution in the water column and sediments, including small-size fractions (<200 μm), are needed to better assess the level of plastic pollution and its fate in the Canary Islands. Overall, this review confirms that the Canary Archipelago is a hotspot of oceanic plastic pollution, with concentrations of ...